On the theory of piecemeal tariff reform: the case of pure imported intermediate inputs - Vega, Ramón López; Panagariya, Arvind (American Economic Review, 1992)
What is the effect of a tariff reduction that applies only to a subset of commodities subject to tariffs? This important question was addressed systematically for the first time by James Meade (1955 Ch. 13) in his classic work Trade and Welfare. After a careful analysis, Meade concluded, [T]here is more likely to be a gain in economic welfare if the rate of duty is high on the which will come in in increased and is low on the which will come in in reduced volume (p. 208).' This result was proved formally by Trent J. Bertrand and Jaroslav Vanek (1971), who demonstrated that, in a small open economy, if the highest tariff rate is reduced to the next highest one, welfare will rise provided the import demand for the good with the highest tariff exhibits gross substitutability with respect to all other goods.2 Subsequently, following a different strand of the literature as exemplified in John Green (1961), Tatsuo Hatta (1973, 1977) and Peter Lloyd (1974) independently proved similar results in terms of Hicksian substitutability.3 In deriving their results, Bertrand and Vanek allowed for the use of final goods as intermediate inputs (i.e., interindustry flows).4 However, neither they nor the subsequent writers (including Hatta and Lloyd) allowed for the existence of imported intermediate inputs that are not produced domestically. Therefore, a natural question is whether the piecemeal policy prescription derived by them remains valid in the presence of pure imported intermediates. This question is particularly important for developing countries for two reasons. First, by far the bulk of the of developing countries are intermediate and capital goods. According to the World Bank, during the period 1975-1985 50 percent of developing countries' were accounted for by intermediate inputs, and an additional 30 percent were capital goods. A sizable proportion of both capital and intermediate goods are neither produced nor directly consumed in these countries. Second, the Meade-Bertrand-VanekHatta-Lloyd result has been the cornerstone of trade policy reform in many developing countries, especially during the last decade. In most countries, trade reform has been based on the so-called concertina approach, under which the highest tariffs are reduced to the next highest ones and then to the next highest ones, and so on. Thus, * Lopez: Professor, Department of Agricultural and Resource Economics, University of Maryland, College Park, MD 20742, and consultant, Trade Policy Division, World Bank, 1818 H Street, N.W., Washington, DC 20433; Panagariya: Senior Economist, Trade Policy Division, World Bank, 1818 H Street, N.W., Washington, DC 20433, and Professor, Department of Economics, University of Maryland, College Park, MD 20742. The findings, interpretations, and conclusions in this paper are entirely those of the authors. They do not necessarily represent the views of the World Bank, its Executive Directors, or the countries they represent. The authors are indebted to two referees and Tatsuo Hatta for valuable comments on an earlier draft. IIn this quotation, primary imports refers to the goods on which tariffs are reduced, while secondary imports refers to other importables subject to tariffs. 2Robert Lipsey and Kelvin Lancaster (1956) had proved the basic result of Bertrand and Vanek in a one-factor, three-good model with a Cobb-Douglas utility function. 3More recently, Takashi Fukushima (1979) has proved the validity of the Hatta-Lloyd result when the highest tariff is shared by several commodities, while Rodney Falvey (1988) has done the same in the presence of quantitative restrictions on imports. 4Although Hatta (1973, 1977) did not allow explicitly for interindustry flows, his results can also be shown to be valid in the presence of such flows.